gymnastqueen
New member
- Joined
- Mar 31, 2008
- Messages
- 11
This is what I have so far, but I suspect that either my method is wrong or I have made mistakes in my calculations somewhere, so is this correct and if not why not?
write 3y[sup:2c5qkzad]2[/sup:2c5qkzad]-x-12y+14=0 in standard form
3y[sup:2c5qkzad]2[/sup:2c5qkzad]-x-12y+14=0
3y[sup:2c5qkzad]2[/sup:2c5qkzad]-12y-x+14=0
3[(y[sup:2c5qkzad]2[/sup:2c5qkzad]-4y=4)-4]-x+14=0
3(y-2)[sup:2c5qkzad]2[/sup:2c5qkzad]-12-x+14=0
((3(y-2)[sup:2c5qkzad]2[/sup:2c5qkzad])/-2)-(x/2)=(-2/-2)
((3(y-2)[sup:2c5qkzad]2[/sup:2c5qkzad])/-2)-(x/2)=1
What info does this give me to graphing this equation?
write 3y[sup:2c5qkzad]2[/sup:2c5qkzad]-x-12y+14=0 in standard form
3y[sup:2c5qkzad]2[/sup:2c5qkzad]-x-12y+14=0
3y[sup:2c5qkzad]2[/sup:2c5qkzad]-12y-x+14=0
3[(y[sup:2c5qkzad]2[/sup:2c5qkzad]-4y=4)-4]-x+14=0
3(y-2)[sup:2c5qkzad]2[/sup:2c5qkzad]-12-x+14=0
((3(y-2)[sup:2c5qkzad]2[/sup:2c5qkzad])/-2)-(x/2)=(-2/-2)
((3(y-2)[sup:2c5qkzad]2[/sup:2c5qkzad])/-2)-(x/2)=1
What info does this give me to graphing this equation?